Revisiting Vision Rehabilitation - Meyniel, Claire; Bodaghi, Bahram; Robert, Pierre-Yves (Frontiers in Systems Neuroscience, 2017)
Low vision is a condition caused by eye or brain disease, in which visual acuity is 20/70 (3/10 or 6/18) or poorer in the better-seeing eye and cannot be corrected or improved with regular eyeglasses. It impacts personal ability to perform vision-dependent tasks as activities of daily living, walking, reading or using a computer. Rehabilitation is a multidisciplinary training dedicated to improve patients’ functional abilities and quality of life. It has to be personalized to every individual situation, whatever the underlying pathology.